Stable oxygen isotopes in Romanian oak tree rings record summer droughts and associated large-scale circulation patterns over Europe - Neil Loader (Climate Dynamics, 2018)
We present the first annual oxygen isotope record (1900 – 2016) from the latewood (LW) cellulose of oak trees (Quercus robur) from NW Romania. As expected, the results correlate negatively with summer relative humidity, sunshine duration and precipitation and positively with summer maximum temperature. Spatial correlation analysis reveals a clear signal reflecting drought conditions at a European scale. Interannual variability is influenced by large-scale atmospheric circulation and by surface temperatures in the North Atlantic Ocean and the Mediterranean Sea. There is considerable potential to produce long and well-replicated oak tree ring stable isotope chronologies in Romania which would allow reconstructions of both regional drought and large-scale circulation variability over southern and central Europe.